Pengaruh Influencer Marketing, Digital Marketing, dan Brand Image Pada Minat Beli Konsumen Tokopedia - Pebrina Paska Yanti Tambunan; Hikmah Hikmah (eCo-Buss, 2024)
This study aims to examine the influence of influencer marketing, digital marketing, and brand image on consumer purchase intention on the Tokopedia e-commerce platform. A quantitative research method with a replication approach was conducted in Batam City, Riau Islands, involving 204 Tokopedia users as respondents. Data were collected through questionnaires and analysed using SPSS version 26. The findings indicate that influencer marketing, digital marketing, and brand image significantly influence consumer purchase intention on Tokopedia. Data analysis shows good validity and reliability for all variables studied. Normality tests indicate that the data are normally distributed, and multicollinearity tests confirm no issues among the independent variables. These findings provide insights into the critical roles of digital marketing strategies and brand image management in influencing consumer purchasing behaviour on Tokopedia. Practical implications highlight the importance for Tokopedia to continually optimize digital marketing strategies and enhance brand image quality to support growth and competitive advantage in the competitive e-commerce market. Moreover, the study contributes to the existing literature by emphasizing the specific mechanisms through which influencer marketing and digital strategies shape consumer perceptions and behaviours in the online marketplace. Future research could explore additional variables or conduct longitudinal studies to further understand the evolving dynamics of consumer behaviour in the digital age.